Surface Interactions Of Polymer Nanoparticles In Waxy Crude Oil Model System - Hasbullah, Nurul Anis (Universiti Sains Malaysia, 2022)
At present, the clogging of wax in pipelines is the most challenging issue to solve, which affecting numerous oil and gas companies since 1920s, due to the low temperature of subsea pipelines which caused undesired phenomenon of wax crystallization. The aim of this study is to evaluate the effect of sodium dodecyl sulphate (SDS) concentration on the stability of poly(methyl methacrylate)-graphene oxide (PMMA-GO) emulsions, to characterize and identify the surface interaction of PMMA-GO and to study the performance of PMMA-GO on oil stabilization by evaluating the surface interaction in different viscosity system. The PMMA-GO is synthesized via emulsion polymerization with ultrasonication having a fixed amount of potassium persulphate (KPS) initiator and varying concentrations of graphene oxide (GO) and sodium dodecyl sulphate (SDS) from range of 0.1 to 1.0 wt%. The samples were characterized using Fourier transform infrared spectroscopy (FTIR) analysis, Ultraviolet-Visible Spectrophotometry (UV-Vis) analysis, Particle Size Analysis, Zeta Potential analysis and Differential Scanning Calorimetry (DSC) analysis. For the application stage, the performance of PMMA-GO on oil stabilization will be evaluated using Zeta Potential analysis by applying hexane and decane as a crude oil model system. We discovered that the increasing SDS and GO concentration promotes better stability of emulsion as the zeta potential increases as well as having good thermal stability. The significance of this study will give vital information on approaches to inhibit wax crystallization of crude oil by means of surface interaction of polymer nanoparticles and at the same time, improve the emulsion stability.